Hypertriglyceridemia Induced Acute Pancreatitis in Pregnancy: A Case Report - Adhikari, Anjali Subedi; Gurung, Sonam (Journal of Lumbini Medical College, 2020)
Introduction: Acute pancreatitis is a rare event in pregnancy. Hypertriglyceridemia induced acute pancreatitis accounts for the second most common cause in pregnancy. This rare event has a high maternal and fetal mortality of 20% and 50% respectively. Case report: A 21-year-old woman, G2P0+1 at 26 weeks period of gestation presented to OBGYN emergency in a state of shock with history of sudden onset of severe epigastric pain and multiple episodes of vomiting for one day and absent fetal movement for six hours. Immediate fluid resuscitation was done. Her reports showed increased hematocrit, leukocytosis, serum lipase and amylase elevated to > 200U/L. Ultrasonography showed bulky pancreas with intrauterine fetal death. With the diagnosis of acute pancreatitis with fetal demise, she was managed conservatively in intensive care unit by fasting, nasogastric aspiration, intravenous fluids, antibiotics, analgesics and heparin. She was intubated on the third day for increasing tachypnea. Her lipid profile showed elevated triglyceride> 1000 mg/dl and was started on oral hypolipidemic drugs. Pregnancy was terminated vaginally by misoprostol and was discharged on 19th day. Conclusion: Hypertriglyceridemia induced acute pancreatitis in pregnancy has an increased maternal and fetal complication.